Polaron states at arbitrary coupling regimes in rectangular potential well - Pocatilov, Evghenii (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2005)

(untitled)
We report here a new approach to the confined polaron problem at arbitrary coupling